Baroreflex dysfunction and augmented sympathetic nerve responses during mental stress in veterans with post‐traumatic stress disorder. (14th June 2017) - Park, Jeanie; Marvar, Paul J.; Liao, Peizhou; Kankam, Melanie L.; Norrholm, Seth D.; Downey, Ryan M.; McCullough, S. Ashley; Le, Ngoc‐Anh; Rothbaum, Barbara O.
Abstract : Key points: Patients with post‐traumatic stress disorder (PTSD) are at a significantly higher risk of developing hypertension and cardiovascular disease. The mechanisms underlying this increased risk are not known. Studies have suggested that PTSD patients have an overactive sympathetic nervous system (SNS) that could contribute to cardiovascular risk; however, sympathetic function has not previously been rigorously evaluated in PTSD patients. Using direct measurements of sympathetic nerve activity and pharmacological manipulation of blood pressure, we show that veterans with PTSD have augmented SNS and haemodynamic reactivity during both combat‐related and non‐combat related mental stress, impaired sympathetic and cardiovagal baroreflex sensitivity, and increased inflammation. Identifying the mechanisms contributing to increased cardiovascular (CV) risk in PTSD will pave the way for developing interventions to improve sympathetic function and reduce CV risk in these patients. Abstract: Post‐traumatic stress disorder (PTSD) is associated with increased cardiovascular (CV) risk. We tested the hypothesis that PTSD patients have augmented sympathetic nervous system (SNS) and haemodynamic reactivity during mental stress, as well as impaired arterial baroreflex sensitivity (BRS). Fourteen otherwise healthy Veterans with combat‐related PTSD were compared with 14 matched Controls without PTSD.  Muscle sympathetic nerve activity (MSNA), continuous blood pressure (BP) and electrocardiography were measured at baseline, as well as during two types of mental stress:  combat‐related mental stress using virtual reality combat exposure (VRCE) and non‐combat related stress using mental arithmetic (MA). A cold pressor test (CPT) was administered for comparison. BRS was tested using pharmacological manipulation of BP via the Modified Oxford technique at rest and during VRCE. Blood samples were analysed for inflammatory biomarkers. Baseline characteristics, MSNA and haemodynamics were similar between the groups. In PTSD vs . Controls, MSNA (+8.2 ± 1.0  vs . +1.2 ± 1.3 bursts min –1, P  < 0.001) and heart rate responses (+3.2 ± 1.1  vs . −2.3 ± 1.0 beats min –1, P  = 0.003) were significantly augmented during VRCE.  Similarly, in PTSD vs . Controls, MSNA (+21.0 ± 2.6  vs . +6.7 ± 1.5 bursts min –1, P  < 0.001) and diastolic BP responses (+6.3 ± 1.0  vs . +3.5 ± 1.0 mmHg, P  = 0.011) were significantly augmented during MA but not during CPT ( P  = not significant). In the PTSD group, sympathetic BRS (–1.2 ± 0.2  vs . –2.0 ± 0.3 burst incidence mmHg −1, P  = 0.026) and cardiovagal BRS (9.5 ± 1.4  vs . 23.6 ± 4.3 ms mmHg −1, P  = 0.008) were significantly blunted at rest. PTSD patients had significantly higher highly sensitive‐C‐reactive protein levels compared to Controls (2.1 ± 0.4  vs . 1.0 ± 0.3 mg L −1, P  = 0.047). Augmented SNS and haemodynamic responses to mental stress, blunted BRS and inflammation may contribute to an increased CV risk in PTSD. Key points: Patients with post‐traumatic stress disorder (PTSD) are at a significantly higher risk of developing hypertension and cardiovascular disease. The mechanisms underlying this increased risk are not known. Studies have suggested that PTSD patients have an overactive sympathetic nervous system (SNS) that could contribute to cardiovascular risk; however, sympathetic function has not previously been rigorously evaluated in PTSD patients. Using direct measurements of sympathetic nerve activity and pharmacological manipulation of blood pressure, we show that veterans with PTSD have augmented SNS and haemodynamic reactivity during both combat‐related and non‐combat related mental stress, impaired sympathetic and cardiovagal baroreflex sensitivity, and increased inflammation. Identifying the mechanisms contributing to increased cardiovascular (CV) risk in PTSD will pave the way for developing interventions to improve sympathetic function and reduce CV risk in these patients.